Dictyostelium discoideum: A Model System for Neurological Disorders - Claire Louise Storey; Robin Simon Brooke Williams; Paul Robert Fisher; Sarah Jane Annesley (Cells, 2022)
Background: The incidence of neurological disorders is increasing due to population growth and extended life expectancy. Despite advances in the understanding of these disorders, curative strategies for treatment have not yet eventuated. In part, this is due to the complexities of the disorders and a lack of identification of their specific underlying pathologies. Dictyostelium discoideum has provided a useful, simple model to aid in unraveling the complex pathological characteristics of neurological disorders including Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, neuronal ceroid lipofuscinoses and lissencephaly. In addition, D. discoideum has proven to be an innovative model for pharmaceutical research in the neurological field. Scope of review: This review describes the contributions of D. discoideum in the field of neurological research. The continued exploration of proteins implicated in neurological disorders in D. discoideum may elucidate their pathological roles and fast-track curative therapeutics.